How does practice change across the season? A descriptive study of the training structures and practice activities implemented by a professional Australian football team. Issue 1 (February 2022) - Tribolet, Rhys; Sheehan, William Bradshaw; Novak, Andrew Roman; Watsford, Mark Langley; Fransen, Job
There is limited research investigating objective practice monitoring in team sports. This observational study examined the practice activities used by eight professional coaches across 72 different practice sessions in one season within a professional Australian football team. This study aimed to evaluate the extent to which these practice types differed from those shown to facilitate skill acquisition in team sports. Across the whole season (pre-season and in-season), coaches implemented seven practice types which were categorised into training-form and playing-form. Practice type frequencies were different between pre- and in-season (χ 2 = 109.6, p < 0.001). Significant differences were reported for practice type duration between pre-season and in-season (p = 0.023, d=–0.17), where in-season activities were longer. Coaches implemented a higher percentage of practice time to playing-form activities in-season (62.0± 25.4) compared to pre-season (52.4± 19.8) [95%CI: –2.35:21.4]. Coaches were more likely to alter the frequency of practice types, rather than the exposure time. Players performed more training-form activities during pre-season than in-season (χ 2 = 30.8, p < 0.001). There were no differences in playing-form activities between pre- and in-season. This study provides insights into the practice activities implemented by professional Australian football coaches and discusses the extent to which they represent best practice in the context of skill acquisition.